Pendekatan Konseling Kelompok Person Centered Teknik Expressive Writing untuk Meningkatkan Konsep Diri Remaja - Lamriama Putri Lestari Limbong; Wahyu Widyatmoko; Dwi Sona; Nuril Hidayanti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This research is motivated by the importance of self-concept, which is seen as the primary foundation for adolescent personal development. However, field observations indicate that not all adolescents are able to develop a positive self-concept. Therefore, this study aims to compare differences in adolescent self-concept levels before and after being treated with person-centered group counseling services using the expressive writing technique. The research was an experimental study using a one-group pretest-posttest design. A sample of six students was selected using purposive sampling. Based on pre-test and post-test data, the mean score before treatment was 85, which is considered low, and after treatment, it showed an increase with a mean score of 134.67. The paired t-test analysis obtained a significance value of 0.000 <0.05, indicating a difference in adolescent self-concept levels before and after being treated with the expressive writing technique for seven sessions. These results indicate that person-centered group counseling services using the expressive writing technique can improve adolescent self-concept.